Techno-Economic Analysis on the Production of Copper Oxide Nanoparticles by Green Synthesis Method using Abultion indicum Leaf Extract on an Industrial Scale - R F Putra; C Satari; R S Sidqi; S R Putri; A B D Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this study was to evaluate the economic feasibility of producing copper oxide (CuO) nanoparticles using the green synthesis method on an industrial scale for 10 years by evaluating from an engineering and economic perspective. Various economic parameters are used to analyze economic viability, including Gross Profit Margin (GPM), Cumulative Net Present Value (CNPV), Payback Period (PBP), as well as economic variations in sales, taxes, raw materials, labor wages, and utilities to ensure project feasibility. Technical analysis to produce 100 kg of CuO nanoparticles per day requires a total production cost of 220,322.850.00 IDR and the gross profit margin is 16,721,250.000,00 IDR per year. PBP analysis shows that the investment will be profitable after more than three years. This project can compete with PBP capital market standards because of the short investment return. The profit is relatively economical, so this project can be run for 10 years under ideal conditions. This research is expected to be a reference for technical and economic analysis of industrial-scale production of CuO nanoparticles